2022
DOI: 10.1016/j.toxrep.2021.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative toxicity, phytochemistry, and use of 53 Philippine medicinal plants

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 141 publications
0
13
0
1
Order By: Relevance
“…They studied various parts of the same plant and reported that cytotoxicity level varies with plant parts. Previously, alkaloids had also been reported for higher toxicity [ 45 ]. Alkaloids including boldine, caffeoylcholine, glycocitridine, anabasamine, and convolidine were tentatively identified only in Muntries.…”
Section: Resultsmentioning
confidence: 99%
“…They studied various parts of the same plant and reported that cytotoxicity level varies with plant parts. Previously, alkaloids had also been reported for higher toxicity [ 45 ]. Alkaloids including boldine, caffeoylcholine, glycocitridine, anabasamine, and convolidine were tentatively identified only in Muntries.…”
Section: Resultsmentioning
confidence: 99%
“…According to scientific reports, any compound or drug with the oral LD50 estimate greater than 1 g/kg could be considered less toxic and safe. 25 Arising from this documented evidence, the hot tea infusion of Moringa stenopetala leaves at an oral dose of 5 g/kg could be seen as moderately safe on acute exposure. The present findings reveal that the hot tea infusion has blood glucose-lowering and antioxidant effects with wide safety of margin.…”
Section: Discussionmentioning
confidence: 94%
“…Several phytomolecules, including flavonoids, total phenolic compounds, alkaloids, glycosides, saponins, glycolipids, dietary fibers, polysaccharides, peptidoglycans, carbohydrates, amino acids, and others obtained from various plant sources, have been reported as potent hypoglycemic and antihyperglycemic agents. 25 Alkaloids, flavonoids, and saponins, which are present in the hot tea infusion of the leaves of Moringa stenopetala , have been linked with the antidiabetic activity of Moringa stenopetala leaves. 18 , 26 At this juncture, however, it is practically impossible to determine the specific phytochemical that bring about the detected antihyperglycemic activity of the Moringa stenopetala leaves of hot tea infusion.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of tannins, alkaloids, steroids, flavonoids, and saponins in M. esculenta leaves extract was discovered by a phytochemical investigation (Clemen-Pascual et al, 2022). Plant phytochemical compounds assess the medicinal value of plant leaves.…”
Section: Phytochemical Compounds Of Cassava (Manihot Esculenta) Leavesmentioning
confidence: 99%